A Pre and Postnatal Physical Therapy Protocol for Recreational Athletes: A Case Series - Rachel Selman; Kate S. Early (North American Sports Medicine Institute, 2024)
# Background and Purpose Recent changes to medical recommendations for exercise in pregnancy and postpartum have expanded to include recreational athletes. While women are transitioning into motherhood at the height of their athletic careers, there is limited guidance on musculoskeletal training from pregnancy through safe return to activity. The lack of education and support in this population may lead to increased prevalence of symptoms and delay of treatment, ultimately hindering athletic performance. The purpose of this case series is to assess pelvic floor symptoms through implementing a new pre- and postnatal exercise training paradigm in a group of women aiming to return to recreational athletics. # Study Design Case series # Methods Six recreationally athletic women between 25-35 years of age were referred to physical therapy during pregnancy to participate in this protocol. The women completed a standardized pregnancy and postpartum rehabilitation plan focused on core and pelvic floor control in addition to specific strength and mobility training. # Results Pain, urinary dysfunction, and pelvic floor muscle strength were assessed at six weeks postpartum and at discharge. Meaningful improvement was noted in pain, urinary dysfunction, and muscle strength by the time of discharge. # Conclusion The decrease in symptoms and improvements in measures of musculoskeletal health suggests that a physical therapist guided rehabilitation protocol may be useful as part of the standard of care to reduce prevalence of pain and dysfunction, particularly in the recreational athlete population. Improving understanding of exercise training in this population may minimize musculoskeletal symptoms and encourage additional research to improve the standard of care for this group of patients. # Level of Evidence Level 4